A novel associative classification model based on a fuzzy frequent pattern mining algorithm. Issue 4 (March 2015) - Antonelli, Michela; Ducange, Pietro; Marcelloni, Francesco; Segatori, Armando
Highlights We propose a novel efficient fuzzy associative classification approach. We exploit a fuzzy version of the FP-Growth algorithm. We perform an experimental analysis on 17 classification datasets. We compare our approach with three well-known associative classifiers.